Bad Chemistry: Basilisks and Women in Paracelsus and pseudo-Paracelsus. (2nd January 2020) - Newman, William R.
Abstract : The basilisk of the pseudo-Paracelsian De natura rerum is the evil twin of the homunculus. Created from menstrual blood by artificial ectogenesis in an alchemical laboratory, the basilisk embodies the poisonous character traditionally ascribed to catamenial women, but magnified and concentrated by its mode of generation to the degree that it can kill by its glance alone. How does this remarkable thought experiment relate to other instances of the basilisk in the genuine and pseudonymous corpus of Paracelsus? The present paper outlines two primary uses which emerge repeatedly: first, in works other than De natura rerum, the basilisk is used by Paracelsus and his imitators as a means of explaining action at a distance, especially in the case of plague. Relying on a medieval association between the basilisk's deadly gaze and the putative ability of menstruating women to damage mirrors, the genuine Paracelsus links contagious disease to the deleterious action of the female imagination. Second, because the basilisk was traditionally held to be the product of an unnatural birth, being born from an egg laid by a rooster and incubated by a toad, the Paracelsian corpus frequently invokes the monster as a model for unnatural generation in general.